Upaya Hukum Kasasi dan Peninjauan Kembali Perkara Perdata Agama, Ekonmi Syariah dan Jinayah - Mukti Arto (Kencana, 2018)
Upaya Hukum Kasasi dan Peninjauan Kembali Perkara Perdata Agama, Ekonmi Syariah dan Jinayah